Coerência espectral da luz espalhada por átomos frios saturados - Dias, Pablo Gabriel Santos (2020)
The spectrum of radiation resonantly scattered by a strongly-driven two-level system consists of three peaks called the Mollow’s triplet. In the case of cold atoms, we can approximate their energy level structure by a two-level system when the probability of excitation of any other levels is negligible. In this work, we use an interferometric system to verify the phase relationship between the two lateral bands of the Mollow triplet arising from the light scattering of a cold cloud strontium atom. This cloud is obtained using a magneto-optical trap over a narrow strontium transition. The interferometric system works based on the scattering of radiation by a cloud and its mirror image. The contrast amplitude of the interference fringes generated by the superposition of the light scattered by the cloud and its specular image shows the phase relationship between the lateral bands.